2004
DOI: 10.1074/jbc.m407180200
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Transport of Matrix γ-Carboxyglutamic Acid Protein and Bone Morphogenetic Protein-2 in Cultured Human Vascular Smooth Muscle Cells

Abstract: Matrix ␥-carboxyglutamic acid protein (MGP) is a member of the vitamin K-dependent protein family with unique structural and physical properties. MGP has been shown to be an inhibitor of arterial wall and cartilage calcification. One inhibitory mechanism is thought to be binding of bone morphogenetic protein-2. Binding has been shown to be dependent upon the vitamin K-dependent ␥-carboxylation modification of MGP. Since MGP is an insoluble matrix protein, this work has focused on intracellular processing and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 47 publications
2
53
0
1
Order By: Relevance
“…Indication that such transformations could take place in the aortic wall has been provided by Watson et al (11) who showed that a subpopulation of cultured VSMCs were transformed to calcifying vascular cells (CVCs) capable of forming a mineralized matrix. We have shown (12) that BMP-2 and MGP are both synthesized by VSMCs and Murshed et al (13) have shown that MGP synthesized in the vessel wall and not blood born MGP is the in vivo pool of the protein that is active as the vascular calcification inhibitor. These findings emphasize the importance to understand the MGP-BMP-2 interaction in inhibition of vascular calcification.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Indication that such transformations could take place in the aortic wall has been provided by Watson et al (11) who showed that a subpopulation of cultured VSMCs were transformed to calcifying vascular cells (CVCs) capable of forming a mineralized matrix. We have shown (12) that BMP-2 and MGP are both synthesized by VSMCs and Murshed et al (13) have shown that MGP synthesized in the vessel wall and not blood born MGP is the in vivo pool of the protein that is active as the vascular calcification inhibitor. These findings emphasize the importance to understand the MGP-BMP-2 interaction in inhibition of vascular calcification.…”
mentioning
confidence: 79%
“…At the end of the incubation period, cells were harvested and washed in DPBS. MK4 treated and ethanol treated (control) cells were lysed in RIPA buffer and solubilized proteins prepared for isoelectric focusing (IEF) by acetone, TCA and ether/ethanol washes before IEF as described by our laboratory (12). The second dimension 2D-SDS-PAGE for IEF and one-dimentional SDS-PAGE were carried out as described (12) using 8-16% gradient CRITERION gels.…”
Section: Treatment Of Vsmcs With Menaquinone-4 (Mk4) and Isolation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation is thought to be carried out by the Golgi casein kinase. 8,9 It has been suggested earlier that-next to being carboxylated-MGP must be fully phosphorylated at each target serine residue to have its optimal inhibitory activity on soft tissue calcification. 9 Besides the g-carboxylase, the metabolic VK cycle also involves the reductase enzyme VKORC1.…”
mentioning
confidence: 99%
“…8,9 It has been suggested earlier that-next to being carboxylated-MGP must be fully phosphorylated at each target serine residue to have its optimal inhibitory activity on soft tissue calcification. 9 Besides the g-carboxylase, the metabolic VK cycle also involves the reductase enzyme VKORC1. Mutations in the GGCX or VKORC1 genes are associated with a hereditary deficiency of the VK-dependent clotting factors as well as a clinically relevant dosing dependency of anti-coagulants.…”
mentioning
confidence: 99%